Advances and perspectives in near‐infrared fluorescent organic probes for surgical oncology. (15th April 2020) - Xu, Dazhuang; Li, Lei; Chu, Chengchao; Zhang, Xiaoyong; Liu, Gang
Abstract: Surgical resection of solid tumors is currently the most efficient and preferred therapeutic strategy for treating cancer. Despite significant medical, technical, and scientific advances, the complete treatment of this lethal disease is still a challenging task. New imaging techniques and contrast agents are urgently needed to improve cytoreductive surgery and patient outcomes. Tumor‐targeted probes are valuable for guiding a surgical resection of tumor from subjective judgments to visual inspection. Near‐infrared (NIR) fluorescent imaging is a promising technology in preclinical and clinical tumor diagnosis and therapy. The rapid development in NIR fluorophores with improved optical properties, targeting strategies, and imaging devices has brought about prospective study of novel NIR nanomaterials for intraoperative tumor detection. In this review, we summarize the recent development in NIR‐emitting organic fluorophores and cancer‐targeting strategies that specifically target and accumulate in tumors for the molecular imaging of cancerous cells. We believe this technique utilizing new fluorescent probes with an intraoperative optical imaging capacity could provide a more sensitive and accurate method for cancer resection guidance, thereby resulting in better surgical outcomes. This article is categorized under: Diagnostic Tools > in vivo Nanodiagnostics and Imaging Nanotechnology Approaches to Biology > Nanoscale Systems in Biology Abstract : Schematic showing the typical example of structural motifs of NIR fluorescent organic dyes and their modification strategies with various tumor‐targeted groups for imaging‐guided surgical oncology.